Hematological indices in renovascular hypertension: A propensity score matching analysis - Ahmet Seyfeddin Gurbuz; Semi Öztürk (KARE Publishing, 2019)
Objective: Various hematological blood count parameters, including the neutrophil-to-lymphocyte ratio (NLR) and mean platelet volume (MPV), were analyzed to assess differences in patients with renovascular (RVH) and essential hypertension (EH). Methods: A propensity score analysis was performed to match 51 patients with RVH and 173 patients with EH. After matching, 49 pairs of patients were compared. Results: Before matching, patients with RVH had significantly higher NLR values [1.35 (range: 1.14-1.76) vs. 1.05 (range: 0.81-1.3); p<0.001] and MPV [8.7 fL (range: 8.3-9.5 fL) vs. 8.4 fL (range: 7.3-9.2 fL; p=0.002]. After propensity score matching was performed (49 vs 49 patients), age, sex, atherosclerosis risk factors, frequency of atherosclerosis, and the medications used were similar between groups. The NLR was significantly greater in patients with RVH [1.00 (range: 0.76-1.40) vs 1.35 (range: 1.15-1.75; p<0.001]. The MPV did not differ significantly between groups. The NLR was the only parameter independently associated with RVH in a multivariate logistic regression [odds ratio: 5.563, 95% confidence interval (CI): 2.089-14.814; p≤0.001]. Receiver operating characteristic curve analysis results indicated that NLR >1.16 predicted RVH with a sensitivity of 72% and a specificity of 60% [area under curve: 0.724, 95% CI: 0.624-0.823; p≤0.001]. Conclusion: The results of the present study demonstrated that NLR, which is a simple, clinical parameter of inflammation, was elevated in patients with RVH.